An evaluation of Regional Fisheries Management Organization at-sea compliance monitoring and observer programs. (May 2020) - Ewell, Christopher; Hocevar, John; Mitchell, Elizabeth; Snowden, Samantha; Jacquet, Jennifer
Abstract: Independent onboard monitoring of fishing activities is important in an era of marine animal overexploitation and declining fish populations. Fisheries observers have traditionally filled this role to varying capacities. Their work is critical to fisheries managers because observers collect data on, for example, catch composition, discard and by-catch policy compliance, and transshipment activities - data that would otherwise be unreliable if collected from other sources. However, fisheries observers have been subject to human rights and safety violations, including intimidation and assault, and many observers have even disappeared from their vessel assignments. In some cases, remote electronic monitoring (REM) has been deployed to complement or substitute for human observers. This study is the first comparison of existing at-sea compliance monitoring and observer programs for 17 Regional Fisheries Management Organizations (RFMOs), the main institutions that currently exist to manage and conserve fish on the high seas or straddling high seas boundaries. Currently only three RFMOs mandate 100% observer coverage on fishing vessels, and no RFMOs mandate 100% at-sea monitoring coverage using REM. Moreover, no RFMOs mandate full transparency of either human observer or REM data. In addition, no RFMOs include regulations to sufficiently ensure the protection of fisheries observer rights and safety, and only four RFMOs mandate a specific process in the event that an observer disappears or dies. RFMOs are well positioned to mandate comprehensive, independent, and transparent monitoring coverage onboard fishing vessels by utilizing a complementary approach of human observers and REM. This would help ensure better management of fisheries as well as better protection of marine ecosystems and human rights at sea.